HOLISTIC HYGIENE JURISPRUDENCE IN ISLAMIC EDUCATION INSTITUTIONS: INTEGRATING FAITH, SELF, ENVIRONMENT, AND MORAL-SPIRITUAL DIMENSIONS - Yono, Yono; Abrista Devi (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: The background of this research stems from the need to align Islamic teachings with the pressing challenges of cleanliness and environmental preservation. Based on normative analysis of the ideas of Mustafa Abu Sway and Abdullah Qasim al-Washli, this study expands the interpretation of Quranic texts and Hadith. Purpose: This research discusses the concept of holistic hygiene jurisprudence in Islamic educational institutions, focusing on the cleanliness of faith, self, environment, and moral-spiritual dimensions. Method: The research employs a literature review and phenomenological approach, using secondary sources such as the Quran, Hadith, and fiqh texts from renowned scholars. Interviews at the Darul Muttaqien Islamic Boarding School in Bogor, Indonesia, serve as the primary data source. Result: The findings support Imam al-Ghazali's view of integrating various aspects of cleanliness, with an emphasis on environmental hygiene as part of nature conservation. This framework aligns with Tu Wei Ming's anthropocosmic perspective, which places humans as an integral part of nature, and counters the anthropocentric paradigm that contributes to environmental degradation. Conclusion: This study highlights the application of holistic hygiene practices in Islamic education, offering a model for integrating faith, personal hygiene, environmental care, and moral-spiritual purity in educational settings.